Production and Characterization of a Polymer from Arthrobacter sp - Bodie, Elizabeth A. (1985)
An Arthrobacter sp. isolated from a glucose-sucrose agar plate was found to produce a neutral, extremely viscous, opalescent extracellular polymer. Growth, polymer production, and rheological properties and chemical composition of the isolated polymer were examined. The polymer was found to be substantially different from other arthrobacter polymers. Some unusual properties included irreversible loss of viscosity with high temperature and degradation of the polymer during fermentation and upon storage at 4°C. Other characteristics included dependence on sucrose for polymer production, relative pH stability, increased viscosity with increased salt concentration, and pseudoplasticity. The polymer was found to be composed primarily (if not entirely) of d-fructose. The fructose content and other characteristics suggested that the polymer was a levan.